The truth about violence (horizon) - Portillo, Michael; Petterlo, Diene ([Australia] : BBC Active, 2006)
This program discovers the terrifying violence that lies within us all. from the role brain chemicals like dopamine and serotonin play in controlling our aggression to social
Title from container
Editor, Andrew Cohen ; camera, Chris Openshaw, Kevin white ; sound, Andrew Yarme, George McMillan
Narrated by Paul McGann
DVD Format
Keywords: Violence; Violence in children; Violence in adolescence